PURIFIKASI DAN KARAKTERISASI MANANASE DARI Saccharopolyspora flava 76 - , Wahyu Wido Sari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mannan is one of major component of hemicelluloses that consist of mannose, galactose, and glucose with Î²-1,4 linkage. Mannanase catalyzes hydrolysis of mannan to mannose and manooligosaccharides. These mannose and manooligosaccharides have potential as functional food. Saccharopolyspora flava 76 is belong to Biotechnology Culture Collection (BTCC)-LIPI, have ability to produce mannanase. This research aims at finding purification steps for that enzyme, characterize and analyse the hydrolysis of porang flour to oligosaccharides by the mannanase. There are some steps in this research: (i) qualitative and quantitative analyze of mannanase produced by S. flava 76, (ii) production optimation, (iii) production and extraction of the enzyme, (iv) purification,(v) characterization, and (vi) analysis of the ability of mannanase enzymes hydrolyze porang flour into oligosaccharides. The isolate has an mannanolitic index 4,63 and the highest enzyme activity of 2,47 U/ml on the fourth days at 0,3% LBG substrate with addition 0,1% of mannose. The purification consist of three step, concentration with poly etilene glycol 6000 (PEG 6000), ammonium sulfate precipitation, and gel filtration chromatography with Sephadex G-75. Using PEG 6000 the enzyme activity rose to 3,59 times and rose again 3,84 times after precipitated by 60% ammonium sulfate. This purified enzyme was identified as Î²-mannanase based on its characteristics that was optimum pH in neutral (7,0) phosphate buffer, optimum temperature at 50 Â°C, molecular weight in 50 kDa and 60 kDa by SDS-PAGE, the kinetic of this enzyme was Km = 0,505 mg/ml and Vmax = 0,732 Âµmol/hour, and its ability to hydrolyzed porang flour (glucomannan) to abundant mannooligosaccharides such as mannotriose, mannoheptose and monosaccharides such us mannose and glucose in small quantities product.